2021
DOI: 10.3389/fphar.2020.583528
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs as Biomarkers and Therapeutic Targets for Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is the most common diabetic complication and is a leading cause of end-stage kidney disease. Increasing evidence shows that DKD is regulated not only by many classical signaling pathways but also by epigenetic mechanisms involving chromatin histone modifications, DNA methylation, and non-coding RNA (ncRNAs). In this review, we focus on our current understanding of the role and mechanisms of ncRNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 179 publications
0
20
0
Order By: Relevance
“…In addition, a novel Smad3-dependent long non-coding RNA Erbb4-IR showed various actions in prostate and esophageal squamous cell carcinoma, where one of the actions is to inhibit apoptosis by downregulating tumor suppressor miRNA-145, thus promoting cancer cell proliferation [ 68 , 144 ]. Upregulation of TGF-β/Smad-mediated Erbb4-IR and LRNA9884 were observed in renal fibrosis, as they up-regulate the pathogenic effectors via transcriptional regulation at genomic level [ 145 , 146 , 147 , 148 ]. The pathogenic roles of inflammatory cells in the TGF-β-mediated tissue fibrosis have been intensively elucidated especially on the innate immunity, e.g., macrophage, neutrophil, etc.…”
Section: Future Prospectmentioning
confidence: 99%
“…In addition, a novel Smad3-dependent long non-coding RNA Erbb4-IR showed various actions in prostate and esophageal squamous cell carcinoma, where one of the actions is to inhibit apoptosis by downregulating tumor suppressor miRNA-145, thus promoting cancer cell proliferation [ 68 , 144 ]. Upregulation of TGF-β/Smad-mediated Erbb4-IR and LRNA9884 were observed in renal fibrosis, as they up-regulate the pathogenic effectors via transcriptional regulation at genomic level [ 145 , 146 , 147 , 148 ]. The pathogenic roles of inflammatory cells in the TGF-β-mediated tissue fibrosis have been intensively elucidated especially on the innate immunity, e.g., macrophage, neutrophil, etc.…”
Section: Future Prospectmentioning
confidence: 99%
“…Available evidence has indicated the important roles of lncRNAs in the pathophysiology of diabetic kidney disease (DKD), and the crosstalk between lncRNAs and DKD were reported in recent years [15][16][17][18][19]. Altered expression levels of lncRNAs play key roles in the development of proteinuria and associated diabetic nephropathy (DN) [15,20].…”
Section: Lncs In Diabetic Kidney Diseasementioning
confidence: 99%
“…Available evidence has indicated the important roles of lncRNAs in the pathophysiology of diabetic kidney disease (DKD), and the crosstalk between lncRNAs and DKD were reported in recent years [15][16][17][18][19]. Altered expression levels of lncRNAs play key roles in the development of proteinuria and associated diabetic nephropathy (DN) [15,20]. LncRNAs are involved in the progression of kidney disease through regulation of many important factors, such as pathologic processes in mesangial cells, podocytes, reactive oxidative species, epithelial-to-mesenchymal transition (EMT), endothelial-to-mesenchymal transitions (EndMT) and actions on microRNAs [21][22][23].…”
Section: Lncs In Diabetic Kidney Diseasementioning
confidence: 99%
“…As previously mentioned, the group of lncRNAs identified in kidneys is highly specific to cell type or disease state. Studies carried out over these years have identified a group of anti- or pro-fibrotic and inflammatory lncRNAs in diabetic, acute and chronic renal diseases ( Tang et al, 2017 , 2018a ; Ren et al, 2019 ; Gu et al, 2020c ) ( Table 1 ).…”
Section: The Emerging Role Of Long Non-coding Rnas In Renal Inflammation and Fibrosismentioning
confidence: 99%